Efficient hydrogen generation on CuO core/AgTiO2 shell nano-hetero-structures by photocatalytic splitting of water. (June 2019) - Sharma, Shailja; Pai, Mrinal R.; Kaur, Gurpreet; Divya,; Satsangi, Vibha R.; Dass, Sahab; Shrivastav, Rohit
Abstract: Efficient hydrogen generation via photocatalytic splitting of water, using methanol as hole-scavenger, has been recorded using CuO core/AgTiO2 shell nano-hetero-structures. Ag incorporation in TiO2 ranged 1, 3, 5 and 7% at. XRD, SEM and TEM analyses of samples confirmed the dominant evolution of tenorite CuO and anatase TiO2 . Average crystallite size was 36, 22 and 33–42 nm for pristine CuO, pristine TiO2 and core/shell samples, respectively. EDX and XPS analyses indicated composition and oxidation states of elements and the existence of Ag in metallic state. Exhibiting absorption in the visible range, diffuse reflectance UV–Visible absorption spectra of core/shell samples resembled closely to that of pristine CuO. Compared to pristine samples, core/shell samples yielded significant gain in hydrogen generation. Sample with 1% Ag-incorporated TiO2 shell recorded most efficient hydrogen generation with yield as high as 180 and 13 μmol g −1 h −1 in laboratory and field conditions, respectively. Plausible reasons for the observed gain in performance are given. Graphical abstract: Image Highlights: CuO core/AgTiO2 shell samples were found better photocatalyst for water splitting. Maximum H2 yield was 180 μmol g −1 h −1 under UV–visible illumination. Under natural solar light, maximum yield was 13 μmol g −1 h −1 . Unique nano-hetero-structure guided efficient flow of photo-induced electron/hole. Pre- and post-catalysis, XRD analysis of samples indicated their high stability.